2008
DOI: 10.1074/jbc.m801943200
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of a Cation-dependent O-Methyltransferase from the Cyanobacterium Synechocystis sp. Strain PCC 6803

Abstract: The coding sequence of the cyanobacterium Synechocystis sp. strain PCC 6803 slr0095 gene was cloned and functionally expressed in Escherichia coli. The corresponding enzyme was classified as a cation-and S-adenosyl-L-methionine-dependent O-methyltransferase (SynOMT), consistent with considerable amino acid sequence identities to eukaryotic O-methyltransferases (OMTs). The substrate specificity of SynOMT was similar with those of plant and mammalian CCoAOMT-like proteins accepting a variety of hydroxycinnamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…In the case of the 3,4,5-trihydroxycinnamic acid, present in the compound 4, an analytical standard was not available and the compound was tentatively identified on the base of its molecular mass. We could not find any precise literature data about its UV maxima, but the UV spectrum we obtained (see Supplementary Figure S196) was similar to one presented in the work of Kopycki et al [16].…”
Section: Figure 2 Structures Of Flavonol Glycosides Isolated From Thsupporting
confidence: 51%
See 1 more Smart Citation
“…In the case of the 3,4,5-trihydroxycinnamic acid, present in the compound 4, an analytical standard was not available and the compound was tentatively identified on the base of its molecular mass. We could not find any precise literature data about its UV maxima, but the UV spectrum we obtained (see Supplementary Figure S196) was similar to one presented in the work of Kopycki et al [16].…”
Section: Figure 2 Structures Of Flavonol Glycosides Isolated From Thsupporting
confidence: 51%
“…In this study we presented the purification and structure elucidation of 18 acylated and non-acylated glycosides of kaempferol and quercetin, including 16 (11). Kaempferol and quercetin are known as potent antioxidants with diverse biological activity and health-promoting properties.…”
Section: Kaempferolmentioning
confidence: 99%
“…The molecular weights of the OMTs in this group range from 23 to 27 kDa. A subgroup within the CCoAOMT-like enzymes is found in plants and microbes (Ibdah et al 2003;Lee et al 2006;Kopycki et al 2008b). They have similar molecular weights compared to classical CCoAOMTs but they utilize both Xavonoids and caVeoyl-CoA.…”
Section: Introductionmentioning
confidence: 98%
“…The recombination proteins were expressed and purified via the method developed by Kim et al 18 The O-methyltransferase assay was conducted as previously described. 11 Reaction mixture contained 60 µM of flavonoid, 500 µM of SAM and 3 µg of the purified wild type ROMT9 or 90 µg of D275L or 65 µg of H328R in 500 µL of 50 mM Tris/HCl (pH 7.5). The reaction mixture was incubated at 37 o C for 30 min.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…However, recent studies have demonstrated that OMTs closely related to CCoAOMT from microorganisms and plants utilized flavonoids more efficiently than caffeoryl-CoA. [9][10][11][12] However, it remains unclear as to whether these OMTs constitute a new group of OMTs. The structures of OMTs of both groups have been determined and the reaction mechanisms of OMTs have been elucidated.…”
mentioning
confidence: 99%